Desafíos nacionales frente a la ciberseguridad en el escenario global: un análisis para Colombia - Milton Ricardo Ospina Díaz; Pedro Emilio Sanabria Range (Revista Criminalidad)
This article covers the topic of information security in light of cybersecurity threats in a global context, reviewing the current situation in Colombia. A historical walk-through on cybersecurity was performed through qualitative, theoretical, documentary and descriptive research (cyberwar, cyberdefense, computer crime), particularly in the component of information security. In addition, various aspects in that regard were worked on (contexts, risk analyses, management systems and quality standards), while risks to businesses, society and countries are shown, demonstrated with the coronavirus (COVID-19) pandemic. In the case of Colombia, data on government action in light of these threats were reviewed and its information security policies and quality standards were researched. Colombia’s challenges from cybersecurity threats, in terms of information security, are shown at the end of the article.